1993
DOI: 10.1254/jjp.63.461
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection of Dynorphin into the Supraoptic and Paraventricular Nuclei Produces Antidiuretic Effects through Vasopressin Release

Abstract: ABSTRACT-The mechanisms for the antidiuretic effects of dynorphin (DYN), an endogenous K-agonist, microinjected into the hypothalamic supraoptic (SON) and paraventricular (PVN) nuclei were investigated. DYN decreased the urine outflow rate dose-dependently from 5 to 20 nmol in the SON and PVN, and it in creased vasopressin release. Microinjection of des-Tyr-DYN (a non-opioid peptide) into the SON produced antidiuretic effects with similar potency to that of the DYN-induced effects. However, in the PVN, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The functional consequence of κ-APJ heteromerization was observed at the level of cell proliferation where treatment with either dynorphin A1-13 or apelin-13 significantly increased the proliferation of cells expressing the heteromer compared with cells expressing individual receptors . Although not much is known about the role of the κ-APJ heteromer in vivo either in normal physiology or during pathology, the distribution of the dynorphin/κ receptor system and of the apelin/APJ system in the nuclei of the hypothalamus involved in regulation of arginine vasopressin release as well in the cardiovascular system (Sherman et al, 1986;Tsushima et al, 1993;Reaux et al, 2001), suggests a potential role for κ-APJ heteromers in cardiovascular regulation.…”
Section: κ Opioid and Apelin Receptor (Apj) Heteromersmentioning
confidence: 99%
“…The functional consequence of κ-APJ heteromerization was observed at the level of cell proliferation where treatment with either dynorphin A1-13 or apelin-13 significantly increased the proliferation of cells expressing the heteromer compared with cells expressing individual receptors . Although not much is known about the role of the κ-APJ heteromer in vivo either in normal physiology or during pathology, the distribution of the dynorphin/κ receptor system and of the apelin/APJ system in the nuclei of the hypothalamus involved in regulation of arginine vasopressin release as well in the cardiovascular system (Sherman et al, 1986;Tsushima et al, 1993;Reaux et al, 2001), suggests a potential role for κ-APJ heteromers in cardiovascular regulation.…”
Section: κ Opioid and Apelin Receptor (Apj) Heteromersmentioning
confidence: 99%
“…Since DYN mRNA is found in the PVN and kappa opioid receptors affect AVP release (Hallbeck, 2000; Tsushima et al, 1993) we made a preliminary attempt to determine if DYN (1–8) could also be measured in this assay. In vitro studies revealed that MS 2 of the doubly charged DYN (1–8) ( m / z transition is 491 → 435) would give the most sensitive MS detection.…”
Section: Resultsmentioning
confidence: 99%
“…Microinjection of dynorphin, U50,488, or DAKLI (Tyr-Gly-Gly-Phe-Leu-Arg-Arg-Ile-Arg-Pro-Arg-Leu-Arg-Gly 5-aminopentylamide) into the paraventricular nucleus produced an antidiuretic effect, as did dynorphin into the supraoptic nucleus (518). Because the action ofdynorphin was reversed by atropine and timolol at both sites and by naloxone only in the paraventricular nucleus, it was concluded that its action in the supraoptic nucleus was not opiate mediated and that both sites involved adrenergic and cholinergic mechanisms (518). It is possible that U50,488 and DAKLI in the paraventricular nucleus also produced nonopiate effects, because DAKLI was not inhibited by naloxone and U50,488 might have responded only to the doses used.…”
Section: Gastrointestinal Renal and Hepatic Functionsmentioning
confidence: 97%